Different Mechanisms of Resistance to Bacillus thuringiensis Toxins in the Indianmeal Moth - Herrero, Salvador (American Society for Microbiology, 2001)
Susceptibility to protoxin and toxin forms of Cry1Ab and the binding of (125)I-labeled Cry1Ab and Cry1Ac has been examined in three Plodia interpunctella colonies, one susceptible (688(s)) and two resistant (198(r) and Dpl(r)) to Bacillus thuringiensis. Toxicological studies showed that the 198(r) colony was 11-fold more resistant to Cry1Ab protoxin than to Cry1Ab activated toxin, whereas the Dpl(r) colony was 4-fold more resistant to protoxin versus toxin. Binding results with (125)I-labeled toxins indicated the occurrence of two different binding sites for Cry1Ab in the susceptible insects, one of them shared with Cry1Ac. Cry1Ab binding was found to be altered in insects from both resistant colonies, though in different ways. Compared with the susceptible colony, insects from the Dpl(r) colony showed a drastic reduction in binding affinity (60-fold higher K(d)), although they had similar concentrations of binding sites. Insects from the 198(r) colony showed a slight reduction in both binding affinity and binding site concentration (five-fold-higher K(d) and ca. three-fold-lower R(t) compared with the 688(s) colony). No major difference in Cry1Ac binding was found among the three colonies. The fact that the 198(r) colony also has a protease-mediated mechanism of resistance (B. Oppert, R. Hammel, J. E. Throne, and K. J. Kramer, J. Biol. Chem. 272:23473–23476, 1997) is in agreement with our toxicological data in which this colony has a different susceptibility to the protoxin and toxin forms of Cry1Ab. It is noteworthy that the three colonies used in this work derived originally from ca. 100 insects, which reflects the high variability and high frequency of B. thuringiensis resistance genes occurring in natural populations.